Ramping Behavior Analysis of Ground Mounted Solar PV Generation in Mae Hong Son, Thailand - Somboon Nuchprayoon (2018)
© 2018 IEEE. This work performs statistical analysis of ramping behavior of 3-MW ground mounted photovoltaic plant in Mae Hong Son, Thailand. The analysis considers the times of ramping occurrences, the diurnal and seasonal effects, the definitions of ramp rates. It is found that the times of ramp up are scattering, while the times of ramp down are clustered in the afternoon. The ramp rates in dry season (November-February) are obviously lower than those in summer (March-June) and wet season (July-October). Meanwhile, the power output and yield in dry season are higher. The time window in computing (or measuring) ramp rate is crucial in evaluating the severity of ramping power.